INFECTION PROCESS OF Fusarium oxysporum FUNGUS: A CAUSE OF DAMPING-OFF ON Acacia mangium’s SEEDLINGS - Widyastuti, Siti Muslimah; Tasik, Susanti; Harjono, Harjono (AGRIVITA Journal of Agricultural Science, 2013)
Fusarium oxysporum is the causal agent of damping-off disease. The fungus attacks seedlings of many plant species, including Acacia mangium. In order to effectively control the disease, detailed information on how the fungus infects seedlings of A. mangium and how the plant responds to the fungal infection is essentially needed. The objectives of this research were to investigate: (1) the infection process of F. oxysporumon seedlings of A. mangium, (2) the defence response of A. mangium seedling to infection by F. oxysporum. The fungal pathogen was identified, followed by performance of pathogenicity test. The infection process was followed by macroscopic observation as well as microscopic observation. The result indicated that fungal spore germination was observed at two-day post inoculation in planta. At four-daypost inoculation, hyphae of F. oxysporum had penetrated the collar root of A. mangium seedling via stomata aperture. In addition, fungal hyphae had grown intercellulary in to the vascular tissue. Correspondingly, hypersensitive response was also detected at the stomata aperture. However, this defence mechanism is not effective in stopping the fungus since F. oxysporum is a necrotropic pathogen. Moreover, accumulation of lignin, but not callose, was observed. Keywords:  Fusarium oxysporum, damping-off, Acacia mangium